2005
DOI: 10.1016/j.stam.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-metal ion sensors using chitosan-capped gold nanoparticles

Abstract: We report a novel strategy for using gold nanoparticles capped with chitosan for sensing ions of heavy metals. Acidic anions (glutamate ions in our case) are expected to cap the nanoparticle surfaces similar to conventional methods of stabilization of gold nanoparticles by citrate ions. The polycationic nature of chitosan enables attachment of the polymer to the negatively charged gold nanoparticle surfaces through electrostatic interactions. Use of chitosan serves dual purpose of providing sufficient steric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(131 citation statements)
references
References 19 publications
0
123
0
1
Order By: Relevance
“…1a, UV-visible absorption spectrum for Au colloid consisting of 1 lM GNPs in the presence of 40 g/L PVP molecules in 1-butanol displayed a strong peak at 526 nm ascribed to surface plasmon resonance (SPR) band (Eustis and El-Sayed 2006;Sugunan et al 2005;Ram and Fecht 2011;Behera and Ram 2012a, b). Whereas absorption spectrum of 1 lM uncapped-GNPs (i.e., without PVP molecules) in 1-butanol exhibits a somewhat redshifted and broad SPR band at 533 nm with a half width at full maximum (HWFM) *65 nm shown in the inset of Fig.…”
Section: Uv-visible and Xps Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…1a, UV-visible absorption spectrum for Au colloid consisting of 1 lM GNPs in the presence of 40 g/L PVP molecules in 1-butanol displayed a strong peak at 526 nm ascribed to surface plasmon resonance (SPR) band (Eustis and El-Sayed 2006;Sugunan et al 2005;Ram and Fecht 2011;Behera and Ram 2012a, b). Whereas absorption spectrum of 1 lM uncapped-GNPs (i.e., without PVP molecules) in 1-butanol exhibits a somewhat redshifted and broad SPR band at 533 nm with a half width at full maximum (HWFM) *65 nm shown in the inset of Fig.…”
Section: Uv-visible and Xps Spectrummentioning
confidence: 99%
“…An organic solvent was chosen in this work because such medium founds to provide low interfacial energies needed for a high degree of control during solution and surface processing is required for synthesis of nano colloids (Balasubramaniam et al 2002). Also it was reported that Au-NPs synthesized in an organic medium offer excellent control over size and possess superior processability (Sugunan et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Again, an organic solvent found to provide low interfacial energies is needed for a high degree of control during solution and surface processing [17]. Also, Au NPs synthesized in an organic medium offer excellent control and uniformity of size and possess exceptional processability [39]. The interaction between Au NPs and PVP molecules in 1-butanol has been studied by using UV-visible spectroscopy, FTIR spectroscopy, emission spectroscopy, XPS, zeta potential, and transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Since chitosan was dissolved in aqueous acidic media, the amine groups of the D-glucosamine repeating units get protonated [1,2]. When diluted Hydroaurochloric acid was added in to chitosan solution, negatively charged gold (III) ions were adsorbed on various chains of chitosan due to electrostatic attraction with positively charged protonated amino groups [3,5]. Generally, the reduction of Au 3+ (aq) to Au 0 follows three electron transfer mechanism [6].…”
Section: Resultsmentioning
confidence: 99%